A synthesis of deimatic behaviour. (8th August 2022) - Drinkwater, Eleanor; Allen, William L.; Endler, John A.; Hanlon, Roger T.; Holmes, Grace; Homziak, Nicholas T.; Kang, Changku; Leavell, Brian C.; Lehtonen, Jussi; Loeffler‐Henry, Karl; Ratcliffe, John M.; Rowe, Candy; et al.
ABSTRACT: Deimatic behaviours, also referred to as startle behaviours, are used against predators and rivals. Although many are spectacular, their proximate and ultimate causes remain unclear. In this review we aim to synthesise what is known about deimatic behaviour and identify knowledge gaps. We propose a working hypothesis for deimatic behaviour, and discuss the available evidence for the evolution, ontogeny, causation, and survival value of deimatic behaviour using Tinbergen's Four Questions as a framework. Our overarching aim is to direct future research by suggesting ways to address the most pressing questions in this field.